Meio ambiente na agenda internacional: Implementaç\~ao no Brasil das convenç\~oes do rio sobre biodiversidade, clima e desertificaç\~ao - Adriana Maria Magalh\~aes de Moura; Gustavo Luedemann; Júlio César Roma; Nilo Luiz Saccaro Junior; José Roberto de Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The challenge of performing environmental governance at the international level has resulted in the creation of several environmental agreements focused on the common interests involved in the management of natural resources among countries. In recent decades, there has been a proliferation of such agreements, which made the environment the second area with the largest number of international agreements in the world (second only to international trade), which indicates the growing importance given to environmental issues in international arenas. Among these agreements, we highlight the result of the United Nations Conference on Environment and Development (Rio-92): the United Nations Framework Convention on Climate Change, the Convention on Biological Diversity and the United Nations Convention to Combat Desertification. This paper presents an overview of the status of implementation of these conventions in Brazil, focusing on the governance framework (institutional and legal), as well as on the actions taken to meet the commitments arising from these agreements. Main gaps and some of the challenges to be faced in the implementation of the analyzed conventions in Brazil are also identified.
Keywords: Q58; 330; international environmental agreements; evaluation of public policies; environment